PENGEMBANGAN MEDIA MOLETAYA (MOBILE LEARNING TATA SURYA) BERBASIS CONSTRUCT 2 UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Andriani, Ika Zulvian; Kurnianto, Bagas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The era of the industrial revolution 4.0 is a challenge in various fields to adapt to technological developments, including education. However, based on the results of observations and interviews conducted, the teacher has not innovated learning media to support the IPAS learning process, which has an impact on learning outcomes that are not optimal. This study aims to describe the design, test and analyze the feasibility, practicality and effectiveness of MOLETAYA (Mobile Learning Solar System) Learning Media Based on Construct 2. The type of research conducted is R&D using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection instruments used material and media expert validation, teacher and student response questionnaires, pretests and postests. The data analysis techniques used were feasibility test, practicality test and effectiveness test. The results of media feasibility get a score of 90% from material experts and 85% from media experts with a “very feasible” category. The practicality of the media by teachers was 94% and 84.7% from students with “very practical” and “practical” categories. Based on the t-test, there is a significant difference in student learning outcomes when before and after using the media. The increase in results obtained an N-Gain value of 59% in the small group and 65% in the large group with a “fairly effective” interpretation.